ANALISIS PELAKSANAAN DIVERSI TERHADAP ANAK PELAKU TINDAK PIDANA KEKERASAN (STUDI PUTUSAN NOMOR 3/Pid.Sus.Anak/2019/PN Rbg) - I Nyoman Budiana; Ni Ketut Ananda Putri Pramessy (Jurnal Hukum Saraswati (JHS), 2025)
This study illustrates the principles of legal protection for children who commit criminal acts in Law of the Republic of Indonesia Number 11 of 2012 concerning the Juvenile Criminal Justice System in Decision Number 3/Pid.Sus.Anak/2019/PN Rbg which refers to the application of sanctions and the principle of protection against children who commit criminal acts. The research method used is normative legal research. The first research result is the provisions for sanctions against children in accordance with those regulated in Law Number 35 of 2014 concerning amendments to Law No. 23 of 2002 concerning Child Protection which states that imprisonment can be applied to children if there is no final effort and it is carried out separately from adult prison. Second, efforts to protect children are carried out by imposing restorative and diversionary sentences if they meet the requirements of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. Third, the implementation of diversion in the judge's decision is considered not optimal because of all the perpetrators, only one received sanctions. Judges in preparing court decisions should adhere to the concepts, principles and basics of restorative justice which prioritizes the restoration or improvement of the parties.